The treatment of stroke: specific management - thrombolysis plus - Wahlgren, Nils (Henry Stewart Talks, 2008)
Global stroke burden, Neurological symptoms, Where do thromboembolic occlusions originate?, Recanalization, Pharmacological treatment, Clinical trials, Treatment indications for intravenous rt-PA, Common misunderstandings, Treatment recommendations, Haemorrhagic complications in routine clinical practice, Multivariate analysis, Risk factors, Intravenous thrombolysis, SITS, Pooled analysis, Thrombolysis and highly specialized interventions require new standards for organized stroke care
Archived at 2018/12/10